Kadar Plumbum Pada Pasta Gigi Cangkang Anadara granosa Dengan Penambahan Citrus medica - Sri Vanrovia Usman; Margaretha Solang; Syam S. Kumaji (Journal Syifa Sciences and Clinical Research, 2022)
This study aims to determine the effect of adding suanggi orange juice (Citrus medica) to the lead content of blood clam shell toothpaste (Anadara granosa). The research was carried out at the Laboratory of the Department of Biology, FMIPA, state University of Gorontalo. This study used a completely randomized design (CRD) consisting of 4 treatments and 3 replications. Data analysis used One Ways Analysis of Variance and Duncan’s test at 5% level. The result showed that the addition of suanggi orange juice reduced the levels of lead in blood clam shell toothpaste (Anadara granosa). The addition of suanggi orange juice significantly reduced the levels of lead (p=0.000). the lead content of toothpaste added with 6 mL of orange suanggi is 0,036 ppm and is below the limit for Pb contamination on toothpaste according to SNI 8816:2020 which is 20.0 mg/kg.